Evaluation of Vascular Parameters in Patients With Pulmonary Thromboembolic Disease Using Dual-energy Computed Tomography. Issue 6 (November 2019) - Nallasamy, Navi; Bullen, Jennifer; Karim, Wadih; Heresi, Gustavo A.; Renapurkar, Rahul D.
Abstract : Purpose: The purpose of this study was to evaluate patterns of vascular and lung parenchymal enhancement in patients with suspected chronic thromboembolic pulmonary hypertension (CTEPH) and in those with acute pulmonary embolism (PE) and compare those two groups. Materials and Methods: We retrospectively studied 186 thoracic DECT studies referred for evaluation of CTEPH or pulmonary hypertension. A total of 80 of these patients had a negative scan (control group), 13 had acute PE, and 53 had chronic thromboembolic disease (CTED)/CTEPH. Five different DECT-based parameters were evaluated that highlight patterns of vascular kinetics. Specifically, total DECT-based parenchymal attenuation in Hounsfield Unit (HU) (LungHU), percentage of perfused blood volume (PBV), peak enhancement of main pulmonary artery (PApeak in HU), maximum enhancement corresponding to 100 (PAmax), and the ratio of PApeak to LungHU were calculated. Results: Compared with patients with negative CT, patients with CTED/CTEPH tended to have lower LungHU (median: 27 vs. 38, P <0.001), lower PBV (median: 39 vs. 51, P =0.003), and higher PApeak/LungHU ratio (median: 17 vs. 13, P =0.003). Compared with patients with acute PE, patients with CTED/CTEPH tended to have lower LungHU (median: 27 vs. 39, P =0.006), lower PBV (median: 39 vs. 62, P =0.023), and higher PApeak/LungHU ratio (median: 17 vs. 11, P =0.023). No statistically significant differences were observed between patients with acute PE and those with negative CT. Conclusions: DECT-based vascular parameters offer the potential to differentiate patients with acute versus chronic PE. These various anatomic and functional vascular DECT-based parameters might be reflective of the state of the underlying vascular bed.